Climate change : international law and global governance. - Ruppel, Oliver Christian, 1969-; Roschmann, Christian; Ruppel-Schlichting, Katharina (Nomos, 2013)
"This two volume study systematically addresses both international climate change law and global climate change governance. It deals with international law and the multiple regulatory regimes which reflect fragmentation in the absence of a universal climate change regime. International climate change law, global climate governance, and diplomacy are interrelated and extremely complex, and each volume explores these areas from a variety of doctrinal, transdisciplinary, and thematic perspectives. *** Volume I [ISBN 978 3 8329 7797 9] assesses the most pressing impacts of climate change on various."--Publisher's description